VD_FINDINFO Jug / 2012 / 12 vom 31. August 2011 - VD Tribunal cantonal (2011)
FIXATION DE LA PEINE, ATTÉNUATION DE LA PEINE, CONCOURS D'INFRACTIONS | 106 al. 3 CP, 19 al. 2 CP, 46 al. 1 CP, 47 CP, 49 al. 1 CP, 49 al. 2 CP